2013
DOI: 10.1111/ajt.12165
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 3 and 7/8 Function Is Impaired in Hepatitis C Rapid Fibrosis Progression Post-Liver Transplantation

Abstract: Recurrence of hepatitis C (HCV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Regarding HCV infection, TLR8 rs3764880 G allele might be responsible for the enhanced immune activation and the improved control of HCV infection, which shall explain the delay of the natural course of HCV infection in patients with rs3764880 G allele infected with GT1. This hypothesis is in consistency with the study of Howell et al, which showed that a reduced immune activation, due to impaired TLR3 and TLR7/8-mediated cytokine responses, entailed an aggressive HCV recurrence and rapid liver fibrosis progression (Howell et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding HCV infection, TLR8 rs3764880 G allele might be responsible for the enhanced immune activation and the improved control of HCV infection, which shall explain the delay of the natural course of HCV infection in patients with rs3764880 G allele infected with GT1. This hypothesis is in consistency with the study of Howell et al, which showed that a reduced immune activation, due to impaired TLR3 and TLR7/8-mediated cytokine responses, entailed an aggressive HCV recurrence and rapid liver fibrosis progression (Howell et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Single nucleotide polymorphisms (SNPs) located within TLR8 have been related with an altered innate immune response, susceptibility to HCV infection (Wang et al, 2011;Wang et al, 2013), and progression of HIV disease (Mackelprang et al, 2014;Oh et al, 2008). HCV may also directly activate the innate immune system via TLR8, leading to chronic inflammation and hepatic fibrosis; and may impair TLR signaling in order to evade clearance and promote chronic infection (Howell et al, 2013). In addition, there are sex differences in innate and adaptive immune response, such as differences in the pathogenesis of infectious diseases, being females less prone to suffer from them.…”
Section: Chronic Hepatitis C (Chc) Represents a Leading Comorbidity Imentioning
confidence: 99%
“…TLR-mediated recognition of HCV infection is considered a significant player in the host antiviral response. Indeed, defective production of TLR3- and TLR7/8-induced cytokines is suspected to be one of the causative factors in aggressive HCV recurrence after liver transplantation, mainly via deregulation of the immune response to HCV, which causes subsequent activation of fibrogenesis (Howell et al 2013). …”
Section: Immune System Responses To Chronic Hepatitis Cmentioning
confidence: 99%
“…Treatment with the TLR3 ligand Poly-I:C enhanced the activation of NK cells for killing HSCs, leading to attenuation of liver fibrosis (107). Recently, impaired TLR3 and TLR7/8 function was reported to affect rapid fibrosis progression post-liver transplantation with HCV infection (108). …”
Section: Role Of Tlrs In Murine and Human Liver Injurymentioning
confidence: 99%